An integration method of MFCA, dynamic programming, and multiple criteria decision making in operations improvement: A case study - C. Kasemset (2018)
© 2017 IEEE. This study proposed an integrated method of three concepts: MFCA, DP, and MCDM in operations improvement. The proposed procedure starts from performing MFCA calculation to evaluate material losses along the current production line and identify operations that need to be improved. The cost of positive product can be calculated for each solution. This value was subsequently used in DP with two additional criteria as the amount of investment and the score of difficulty in implementation. Three criteria were transformed to single objective in DP for finding the optimal solution. To demonstrate the application of the proposed method, one small textile company was selected as a case study. The results showed that the optimal solution was to implement only two from three solutions that can help the company to increase the cost of positive product from 84.26% to 94.73% with less investment and score of the difficulty in implementation.